Appraisal of corporate governance in a lower middle income country: The case of Ghana - Seth Oppong; Rajesh Arora; Paul R. Sachs; Mamuda T. Seidu (Accounting, 2017)
Accountability is instrumental for ensuring that a trusting relationship exists between shareholders and management of corporations in order that there will be enhanced investor confidence. Towards this end, corporate governance measures are instituted to make the executives or management of business organizations accountable for their stewardships of the organizational resources or shareholders’ investments. It is against that backdrop that the Securities and Exchange Commission in Ghana has also developed a code on best practices on corporate governance. However, the extent to which the provisions in the code are consistent with the theoretical and empirical literature is unknown. This paper, therefore, sought to explore whether or not gaps exist between the corporate governance policy and practices in Ghana and extant literature. This paper achieves this by examining characteristics of the board as they exist in Ghana in relations to the literature. The characteristics examined in this paper include responsibilities, optimal size, independence, board composition, and audit and compensation committees of boards. Recommendations are made based on the literature to address gaps that exist.